Molten-salt synthesis of Ba5−xSrxNb4O15 solid solutions and their enhanced humidity sensing properties. Issue 1 (January 2018) - Ji, Guo-Jin; Zhang, Le-Xi; Zhu, Meng-Ya; Li, Si-Meng; Yin, Jing; Zhao, Li-Xin; Fahlman, Bradley D.; Bie, Li-Jian
Abstract: Layered perovskite-type niobates A5 Nb4 O15 (A = Ba, Sr) are thought to be good candidates for microwave dielectric and water-splitting applications, but traditional solid-state syntheses of these compounds usually require high temperatures and complicated procedures. In this work, Ba5−x Srx Nb4 O15 (x = 0 − 5) perovskite solid solutions were obtained using a facile molten salt synthetic method. The crystal structure of Ba5−x Srx Nb4 O15 solid solutions were characterized by X-ray diffraction (XRD). Crystal structure parameters with different Sr 2+ concentrations show that the lattice parameters and unit cell volumes of Ba5−x Srx Nb4 O15 decrease with increasing [Sr 2+ ]. The humidity sensing behavior of Ba5−x Srx Nb4 O15 solid solutions was investigated over a wide relative humidity (RH) range, from 11% to 95%. Ba2 Sr3 Nb4 O15 shows the highest sensitivity among the obtained samples with a humidity hysteresis of ca. 4% RH. The response-recovery times of the Ba2 Sr3 Nb4 O15 sensor are only 2 s and 17 s as the humidity alternates between 11% and 95% RH, respectively, showing excellent potential as a humidity sensing material for practical applications.